2011
DOI: 10.2119/molmed.2011.00248
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Uptake of Recombinant α-Galactosidase A Produced with a Gene-Manipulated Yeast by Fabry Mice Kidneys

Abstract: To economically produce recombinant human α-galactosidase A (GLA) with a cell culture system that does not require bovine serum, we chose methylotrophic yeast cells with the OCH1 gene, which encodes α-1,6-mannosyltransferase, deleted and overexpressing the Mnn4p (MNN4) gene, which encodes a positive regulator of mannosylphosphate transferase, as a host cell line. The enzyme (yr-hGLA) produced with the gene-manipulated yeast cells has almost the same enzymological parameters as those of the recombinant human GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In yeast, mannose phosphorylation occurs, however, the phosphorylated sugars are capped by terminal mannose residues (Ballou 1990 ) that block the binding of M6PR to its ligands. Efforts have been applied to add M6P tag to plant-made enzymes (He et al 2012 ), or increase M6P content or expose the covered M6P in yeast-made enzymes (Chiba et al 2002 ; Tsukimura et al 2012 ). Although the role of MR in the therapeutic outcome of ERT can be α-gal A-specific, our study proposed a possibility that mannose-terminated enzymes produced from these non-mammalian cell systems, without M6P manipulations, may be sufficiently effective for some LSDs in which non-macrophage cells are affected.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, mannose phosphorylation occurs, however, the phosphorylated sugars are capped by terminal mannose residues (Ballou 1990 ) that block the binding of M6PR to its ligands. Efforts have been applied to add M6P tag to plant-made enzymes (He et al 2012 ), or increase M6P content or expose the covered M6P in yeast-made enzymes (Chiba et al 2002 ; Tsukimura et al 2012 ). Although the role of MR in the therapeutic outcome of ERT can be α-gal A-specific, our study proposed a possibility that mannose-terminated enzymes produced from these non-mammalian cell systems, without M6P manipulations, may be sufficiently effective for some LSDs in which non-macrophage cells are affected.…”
Section: Discussionmentioning
confidence: 99%
“…Purified recombinant GLA (yr-hGLA) showed a mammalian-like phosphorylated N-glycans, with a specific activity of 2.0 × 10 6 nmol h −1 mg −1 , similar to that of agalsidase alfa (2.1 × 10 6 nmol h − 1 mg − 1 ). Although the basic structure of N-glycans was different to those of agalsidase alfa, administration to Fabry mice showed that yr-hGLA was distributed to the kidney and liver, reducing the levels of glycosphingolipids in these tissues [94].…”
Section: Recombinant α-Galactosidase Amentioning
confidence: 94%
“…A combination of yeast cultivation optimization, growth medium supplementation, and glyco-engineering allowed the production of a recombinant GLA with a high mannose-6-phosphate content, and expression levels comparable to those observed in mammalian cells [93]. Finally, recombinant GLA was produced in the yeast O. minuta, glyco-engineered through the disruption of OCH1 gene and the overexpression of the S. cerevisiae MNN4 gene [94]. Purified recombinant GLA (yr-hGLA) showed a mammalian-like phosphorylated N-glycans, with a specific activity of 2.0 × 10 6 nmol h −1 mg −1 , similar to that of agalsidase alfa (2.1 × 10 6 nmol h − 1 mg − 1 ).…”
Section: Recombinant α-Galactosidase Amentioning
confidence: 99%
“…The methylotrophic yeast Ogataea minuta , which can utilize methanol as a sole carbon source, is a suitable host for producing exogenous glycoproteins with human‐compatible sugar chains at large scale and low cost (Kuroda, Kobayashi, Tsumura, et al, ; Kuroda, Kitagawa, Kobayashi, et al, ; Kuroda, Kobayashi, Kitagawa, et al, ; Tsukimura, Kawashima, Togawa, et al, ). To date, several recombinant enzymes with potential for clinical use in enzyme replacement therapies have been successfully expressed in O. minuta cells (Akeboshi, Chiba, Kasahara, et al, ; Akeboshi, Kasahara, Tsuji, et al, ; Tsukimura et al, ). Moreover, the endo‐ β ‐ N ‐acetylglucosaminidase (ENGase) of O. minuta has been identified and characterized, and this enzyme represents the first known yeast ENGase (Murakami, Takaoka, Ashida, et al, ).…”
Section: Introductionmentioning
confidence: 99%